On the Radical Historicity of Literature: Althusser versus Bhaskar. Issue 2 (14th March 2016) - Read, Malcolm K.
Abstract : The present article takes as its point of departure the recent tributes to Bhaskar published on the occasion of the latter's death. Laudable and understandable though it was to prioritize the career trajectories of younger scholars, one of the unforeseen consequences was to marginalize those of their more mature colleagues. The latter perforce arrive upon the scene of critical realism already burdened with their own overdetermined legacies, which demand rather more in the way of complex renegotiation. Taking as exemplary his own career path, from a traditional 'lit crit' of empiricist and Hegelian extraction, through psychoanalysis, to structural marxism, the author of the present article focuses upon his own 'Bhaskarian moment', upon the benefits accrued therefrom, but finally upon the difficulty in reconciling structural marxism with critical realism, insofar as the former prioritizes the notion of a social formation, structured on the basis of a mode of production, the latter the individual/structure dichotomy. Bhaskar's subsequent spiritual turn, it is argued, further aggravated the paradigmatic incommensurabilities, with damaging consequences for those younger scholars attempting to steer a course between both traditions.